Tracheal adenoid cystic carcinoma: a case report - Dhambri, Sawsen; Trabelsi, Wejdan Mohamed; Braham, Rim; Dhaha, Mohamed; Ben Zid, Khadija; Nasr, Chiraz; Kedous, Skander (Frontiers in Oncology, 2025)
BackgroundPrimary malignant tumors of the trachea are extremely rare, representing only 0.2% of all respiratory tract tumors. Among them, adenoid cystic carcinoma (ACC) is the second most frequent histological type. Due to its slow growth and misleading symptoms, diagnosis is often delayed.CaseWe report the case of a 42-year-old male, chronic smoker, who presented with progressive dyspnea and mild hemoptysis. Chest CT revealed a 32-mm expansive lesion of the cervical trachea causing 80% stenosis. Bronchoscopy confirmed an intratracheal mass, and biopsy established the diagnosis of tracheal adenoid cystic carcinoma (TACC).ManagementThe patient underwent crico-tracheal resection with total thyroidectomy and central neck dissection. Histopathology confirmed TACC with perineural and angiolymphatic invasion, as well as thyroid gland infiltration, but clear surgical margins. Adjuvant radiotherapy was delivered using volumetric modulated arc therapy to a total dose of 60 Gy.OutcomeThe postoperative course was uneventful, and the patient recovered well. At one-year follow-up, both CT and bronchoscopy confirmed an unobstructed trachea with no evidence of local recurrence or distant metastasis.ConclusionTACC is an uncommon and challenging malignancy requiring multidisciplinary management. Radical surgery with adjuvant radiotherapy remains the optimal strategy to achieve local control, particularly in cases with perineural invasion. Early diagnosis and complete resection are key to improving long-term prognosis.